Ellis Englesberg and the Discovery of Positive Control in Gene Regulation. Issue 2 (1st October 2014) - Hahn, Steven
Abstract: Based on his work with the Escherichia coli l -arabinose operon, Ellis Englesberg proposed in 1965 that the regulatory gene araC was an "activator gene" required for positive control of the ara operon. This challenged the widely held belief in a universal mechanism of negative regulation proposed earlier by Jacob and Monod. For years, Englesberg's model was met with deep skepticism. Despite much frustration with complex ad hoc explanations used to challenge his model, Englesberg persisted until the evidence for positive control in ara and other systems became overwhelming. Englesberg's pioneering work enriched the original operon model and had a lasting impact in opening new and exciting ways of thinking about transcriptional regulation.